1993
DOI: 10.1083/jcb.121.5.1011
|View full text |Cite
|
Sign up to set email alerts
|

Macropinosome maturation and fusion with tubular lysosomes in macrophages.

Abstract: Abstract. Macropinosomes formed by addition of recombinant macrophage colony-stimulating factor (rM-CSF) to mouse macrophages migrate centripetally and shrink, remaining detectable by phase microscopy for up to 15 min. This longevity allowed us to study how macropinosomes age. Macropinosomes were pulse labeled for 1 min with fixable fluorescein dextran (FDxl0f), a probe for fluid phase pinocytosis, and chased for various times. To quantify changes in their antigenic profile, pulse-labeled macropinosomes of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
268
1
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(297 citation statements)
references
References 39 publications
(39 reference statements)
25
268
1
3
Order By: Relevance
“…These contrasting results could be explained considering that the mechanisms that regulate endocytosis might differ in different cells. Supporting this possibility it has been described that, not only the routes for macropinocytosed Ags, but also the sensitivity of macropinocytosis to microtubule and microfilament destabilizing drugs differ between professional phagocytes and other cell types (38,59,(61)(62)(63). However, our observations made in bicarbonate-free medium support that, as observed in other cell types, acidification of cytosol exerts an inhibitory effect on DC endocytosis.…”
Section: Discussionsupporting
confidence: 89%
“…These contrasting results could be explained considering that the mechanisms that regulate endocytosis might differ in different cells. Supporting this possibility it has been described that, not only the routes for macropinocytosed Ags, but also the sensitivity of macropinocytosis to microtubule and microfilament destabilizing drugs differ between professional phagocytes and other cell types (38,59,(61)(62)(63). However, our observations made in bicarbonate-free medium support that, as observed in other cell types, acidification of cytosol exerts an inhibitory effect on DC endocytosis.…”
Section: Discussionsupporting
confidence: 89%
“…We have observed that actinin-4 does indeed bind to filamentous actin and has bundling, but not nucleation, activity (Lotfi and Bean, unpublished observations). In macrophages, actinin-4 is transiently associated with macropinosomes before their fusion with lysosomes, as well as with phagosomes (Araki et al, 2000), suggesting a role for this molecule in two mechanistically similar types of endocytic trafficking (Racoosin and Swanson, 1993). Interestingly, the depletion of actinin-4 or disruption of hrs/actinin-4 interaction results in a decrease in Tf recycling with no effect on EGF recycling or degradation and no effect on internalization of either Tf or EGF.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of sorting nexins (SNXs) promotes tubulation to facilitate cargo recycling and macropinosome maturation 21, 22, 23, 24, 25. As they move deeper into the cytoplasm, macropinosomes acidify and acquire Rab7, Rab21 and lysosome‐associated membrane protein 1 (LAMP1) 26, 27. While there is no consensus as to the final fate of macropinosomes, it has been shown that they can fuse with each other, LEs and LYs, a process that depends on the PI kinase, PIKfyve 26, 28, 29, 30.…”
mentioning
confidence: 99%
“…As they move deeper into the cytoplasm, macropinosomes acidify and acquire Rab7, Rab21 and lysosome‐associated membrane protein 1 (LAMP1) 26, 27. While there is no consensus as to the final fate of macropinosomes, it has been shown that they can fuse with each other, LEs and LYs, a process that depends on the PI kinase, PIKfyve 26, 28, 29, 30. Thus, the cargo is eventually degraded.…”
mentioning
confidence: 99%